Standardized risk-stratified cardiac assessment and early posttransplant cardiovascular complications in kidney transplant recipients - Rajnochova Bloudickova, Silvie; Janek, Bronislav; Machackova, Karolina; Hruba, Petra (Frontiers in Cardiovascular Medicine, 2024)
Introduction Cardiovascular disease (CVD) is the leading cause of morbidity and mortality in kidney transplant recipient (KTR). There is a dearth of standardized guidelines on optimal cardiovascular evaluation of transplant candidates. Methods This single-center cohort study aims to determine the effectiveness of our standardized risk-stratified pretransplant cardiovascular screening protocol, which includes coronary angiography (CAG), in identifying advanced CVD, the proper pretransplant management of which could lead to a reduction in the incidence of major cardiac events (MACE) in the early posttransplant period. Results Out of the total 776 KTR transplanted between 2017 and 2019, CAG was performed on 541 patients (69.7%), of whom 22.4% were found to have obstructive coronary artery disease (CAD). Asymptomatic obstructive CAD was observed in 70.2% of cases. In 73.6% of cases, CAG findings resulted in myocardial revascularization. MACE occurred in 5.6% (N = 44) of the 23 KTR with pretransplant CVD and 21 without pretransplant CVD. KTR with posttransplant MACE occurrence had significantly worse kidney graft function at the first year posttransplant (p = 0.00048) and worse patient survival rates (p = 0.0063) during the 3-year follow-up period compared with KTR without MACE. After adjustment, the independent significant factors for MACE were arrhythmia (HR 2.511, p = 0.02, 95% CI 1.158–5.444), pretransplant history of acute myocardial infarction (HR 0.201, p = 0.046, 95% CI 0.042–0.970), and pretransplant myocardial revascularization (HR 0.225, p = 0.045, 95% CI 0.052–0.939). Conclusion Asymptomatic CVD is largely prevalent in KTR. Posttransplant MACE has a negative effect on grafts and patient outcomes. Further research is needed to assess the benefits of pretransplant myocardial revascularization in asymptomatic kidney transplant candidates.